The Local South American Chicken Populations Are a Melting-Pot of Genomic Diversity - Luzuriaga-Neira, Agusto; Pérez-Pardal, Lucía; O’Rourke, Sean M.; Villacís-Rivas, Gustavo; Cueva-Castillo, Freddy; Escudero-Sánchez, Galo; Aguirre-Pabón, Juan Carlos; Ulloa-Núñez, Amarilis; Rubilar-Quezada, Makarena; Vallinoto, Marcelo; Miller, Michael R.; Beja-Pereira, Albano (Frontiers in Genetics, 2019)
Chicken have a considerable impact in South American rural household economy as a source of animal protein (eggs and meat) and a major role in cultural manifestations (e.g. cockfighting, religious ceremonies, folklore). A large number of phenotypes and its heterogeneity are representative to the rusticity of the environments (from arid to tropical rain forest and high altitude) and agricultural systems (highly industrialized to subsistence agriculture). This heterogeneity also represents the successive introduction of domestic chicken into this subcontinent, which some consider predating Columbus arrival to South America. In this study, we have used next-generation sequencing of restriction site associated DNA to scan for genome-wide variation across 145 South American chicken representing local populations from six countries of South America (Colombia, Brazil, Ecuador, Peru, Bolivia, and Chile). After quality control, the genotypes of 122,801 single nucleotide polymorphisms (SNPs) were used to assess the genomic diversity and interpopulation genetic relationship between those populations and their potential sources. The estimated population genetic diversity displayed the gamefowl has the least diverse population (θπ=0.86; θS=0.70). This population is also the most divergent (FST=0.11) among the South American populations. The allele-sharing analysis and the admixture analysis revealed that the current diversity displayed by these populations resulted from multiple admixture events with a strong influence of the modern commercial egg-layer chicken (ranging between 44 to 79%) . It also revealed an unknown genetic component that is mostly present in the Easter Island population that is also present in local chicken populations from the South American Pacific fringe.